2013
DOI: 10.1179/1743289812y.0000000002
|View full text |Cite
|
Sign up to set email alerts
|

Plastics recycling: insights into life cycle impact assessment methods

Abstract: The increased consumption of plastics in day to day life has a significant impact on the environment. Life cycle assessment (LCA) is widely used to select a sustainable alternative in plastic waste management. The LCA studies on mechanical recycling and energy recovery scenarios showed that recycling resulted in lower emissions and provided benefits to the environment. These results are valid only if the performance of the recycled plastic is equivalent to those of the virgin materials. Many LCA studies have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 23 publications
0
27
0
2
Order By: Relevance
“…The life cycle environmental impacts were determined with a life cycle assessment (LCA) approach. In the last few years, many LCA studies related to waste management in general (Laurent et al, 2014a,b) and plastics recycling in particular (Lazarevic et al, 2010;Rajendran et al, 2012Rajendran et al, , 2013 have been performed. The recycling of plastics originating from WEEE treatment, however, only has been addressed in one study with a simplified representation of the recycling processes (Wäger et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The life cycle environmental impacts were determined with a life cycle assessment (LCA) approach. In the last few years, many LCA studies related to waste management in general (Laurent et al, 2014a,b) and plastics recycling in particular (Lazarevic et al, 2010;Rajendran et al, 2012Rajendran et al, , 2013 have been performed. The recycling of plastics originating from WEEE treatment, however, only has been addressed in one study with a simplified representation of the recycling processes (Wäger et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in many cases incineration with energy recovery represents the better solution than recycling. Only recently it has been demonstrated by lifecycle analysis that recycling is only the preferred option if a minimum of 70-80% of virgin plastics can be replaced whereas otherwise thermal recovery is favourable (Rajendran et al, 2013).…”
Section: Plastics Recyclingmentioning
confidence: 99%
“…It can be further concluded that the amount of energy to propel the recycling cycle must be smaller than the energy that is contained in the processed materials. In particular for (mixed) plastics, which are basically based on petroleum, a thermal recovery might be the better option than recycling if the recycling process consumes more energy that is necessary for producing new materials (Rajendran et al, 2013).…”
Section: Recycling and Thermodynamicsmentioning
confidence: 99%
“…Contudo, as aplicações são voltadas, principalmente, para biopolímeros e biocompósitos [22][23][24][25][26] ; comparação destes com petroquímicos [27,28] ; as vantagens e as desvantagens da reciclagem [6,[29][30][31][32] . Além disso, há trabalhos de escala laboratorial [27] ou de abordagem restrita, usando apenas um indicador (exemplo: pegada de carbono) [31,33,34] .…”
Section: Discussionunclassified